Fetal outcome in relation with Colour Doppler study of middle cerebral artery & umblical artery in intrauterine growth restriction - Nalini, Yellapragada Lakshmi; Jyothirmayi, Koripally; Reddy, Chinthaparthi Mallikarjuna (International Journal of Research in Medical Sciences, 2017)
Background: The failure of the fetus to reach its genetically predetermined growth potential of sonographic estimated fetal weight (EFW) below 10th percentile for gestational age is called IUGR. This common clinical sign is fetal hypoxaemia. Therefore the challenge is to distinguish the constitutionally small but healthy fetus (Physiologically small) from pathologically small growth restricted fetus. Our objective is to study the fetal outcome in relation to Doppler study of middle cerebral artery and umbilical artery in intrauterine growth restriction (IUGR). Methods: The prospective study was conducted on 100 patients with suspected Intrauterine growth restriction. The subjects were evaluated by middle cerebral artery and umbilical artery velocimetries. Since no treatment is of any help to IUGR fetuses, the main stay of treatment still remains the timely delivery. Results: Mothers with abnormal velocimetries undergone more no of C-sections compared with mothers with normal velocimetries. Growth restricted fetuses with abnormal velocimetry in terms of APGAR score are more at risk of poor outcome. The average birth weight of neonates with abnormal Doppler study was lower when compared with neonates with normal velocimetry. Conclusion: With the Colour Doppler, the study of middle cerebral artery flow along with umbilical artery flows was useful in identifying IUGR and managing them in an appropriate way.